CHILDFREE: SOLUSI ATAU KONTROVERSI? (ANALISIS HADIS ANJURAN MEMPERBANYAK KETURUNAN) - Saputra, Doni; Hakim, Luqmanul; Rafika, Alfiah; Firman, Firman (Universitas Islam Negeri Siber Syekh Nurjati Cirebon, 2024)
Childfree is an individual or couple who is married and decides not to have children. This is influenced by several factors which are strong reasons for not having children. The childfree phenomenon itself appeared and was practiced long before entering the 20th century, but the term childfree began. trend in Indonesia In 2020 after several public figures decided not to have children. This research seeks to analyze childfree from an Islamic point of view, efforts to find childfree laws through the arguments of the Koran, hadith, and fiqh. This study used a descriptive qualitative research approach and a type of literature research (Library research). The results of the study show that the decision to be childfree has become the right of every couple, with several strong reasons not to have children, but the arguments in the Koran and the hadith of the Prophet oppose the decision to be childfree. Therefore, one of the goals of marriage is to have children and continue the next generation of ummah, if this childfree decision is not related to Islamic reasons, then the law is not permissible.